Identification of a tissue resident memory CD8 T cell-related risk score signature for colorectal cancer, the association with TME landscapes and therapeutic responses - Li, Jiazheng; Yang, Chao; Zheng, Yongbin (Frontiers in Genetics, 2023)
Backgrounds: The tissue resident memory CD8 T cell (Trm) constitutes an important component of the local immunity. In the context of malignant tumors, mounting evidence also supports the potential anti-tumor property of this cell subset. Therefore, identification of Trm marker genes and exploration of the causative effect of Trm in shaping tumor microenvironment (TME) heterogeneity might provide novel insights for the comprehensive management of cancer patients. Methods: By dissecting a single T cell transcriptome dataset, we acquired marker genes for Trm, which were latter applied to bulk RNA sequencing profiles of two large colorectal cancer (CRC) patient cohorts downloaded from TCGA and GEO databases. First, CRC patients were divided into different Trm clusters using consensus clustering algorithm. Then, we established a Trm-related gene (TRMRG) risk score signature and tested its efficacy in predicting prognosis for CRC patients. Moreover, a sequence of rigorous and robust analyses were also carried out to investigate the potential role of TRMRG risk score in TME remodeling and therapeutic utility of it in CRC treatment. Results: A total of 49 Trm marker genes were identified by analyzing single cell RNA sequencing profiles. First, CRC patients were successfully classified into two Trm clusters with significant heterogeneity in functional enrichment patterns and TME landscapes. Then, we developed a TRMRG risk score signature and divided patients into different risk levels. High risk patients were characterized by attenuated immunogenicity, weakened sensitivity to immunotherapy, as well as adverse clinical outcomes. While low risk patients with advantages in survival exhibited increased immunogenicity, stronger metabolic activity and improved immunotherapeutic responses. Conclusions: Through combinatorial analysis of single cell and bulk RNA sequencing data, the present study identified Trm to play a non-negligible role in regulating the complexity and heterogeneity of TME for CRC. Moreover, the TRMRG risk score signature developed currently was corroborated to be tightly correlated with prognosis and therapeutic responses of CRC patients, thus exhibiting potential application value for clinical practice.